MALACHITE GREEN TRANSPORT USING POLYMER INCLUSION MEMBRANE METHOD WITH co-EDVB AS CARRIER - Aprilia, Kharisma Citra; Safitri , Nurul Ulfa; Rakhman, Khusna Arif; Kiswandono , Agung Abadi (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Malachite green (MG) is a synthetic dye known for its toxic and carcinogenic properties, necessitating effective removal from aquatic environments. This study investigated the use of a polymer inclusion membrane (PIM) containing co-poly(eugenol-divinylbenzene) (co-EDVB) 2% as a carrier for the selective transport of MG. The membrane was prepared by dissolving co-EDVB, polyvinyl chloride, and dibenzyl ether in tetrahydrofuran (THF). Several parameters were evaluated, including the pH of the source phase, the concentration of nitric acid in the receiving phase, membrane thickness, carrier concentration, transport time, and competitive transport in synthetic wastewater. UV-Visible spectrophotometric analysis at a wavelength of 613 nm revealed that the transport efficiency reached 90.95% under optimal conditions: source phase pH 7, 0.50 M HNO₃ in the receiving phase, membrane thickness T54, and 18 hours of transport. In the presence of competing metal ions such as Pb²⁺ and Cu²⁺, the efficiency decreased to 80.79%, confirming the important role of co-EDVB in enhancing transport selectivity and efficiency.